Kontroversi Sekitar Kekhalifaan Ali Bin Abi Thalib - Soraya Rasyid (Rihlah : Jurnal Sejarah dan Kebudayaan, 2015)
Ali’s era was colored by rebellion and chaos which were started from the death of Uthman Ibn Affan. That problem wasn’t resolved by Ali, had resulted the emergence of Jamal war, Siffin war, and there is also a challenge from Khawarij sect to the government of Ali. Jamal war occurred because of the involvement of the various interests from the people who had participated in the war, for example Aisha group involved because of the interests of Abdullah ibn Zubair and Talhah. In the other hand, the reason of Ali involved to that war is just because to maintained the existence of legitimate caliphate and the interests of Muslims. While the Siffin war happened for insubordination of Muawiyah Ibn Abi Sufyan and the sense of discontent against the existence Caliphate and Ali’s political policy against Usman. The war was ended with the tahkim to Ali, and Mu'awiyah got more benefits from that. The loses of Ali not only because the dismissal of him as caliph, but there are a lot of loses that Ali Caliph got, like some of his followers retreated and out of Ali’s line, because they disagree with the tahkim which was originated from the habit of jahiliyah. Those who came out had known as the Khawarij who always opposed Ali and Muawiyah.